Work situations experienced by Family Health Strategy professionals in Ceará-Mirim - Pinto, Erika Simone Galvão; Menezes, Rejane Maria Paiva de; Villa, Tereza Cristina Scatena (Revista da Escola de Enfermagem da USP, 2010)
The purpose of this study was to analyze the work situations experienced by Family Health Strategy (FHS) professionals. This descriptive study was performed in Ceará-Mirim, Rio Grande do Norte state, in 2007. The population consisted of 190 FHS professionals, in which a questionnaire with closed-questions was applied. The results showed that 83.2% of the professionals consider that knowing the geographical area under their responsibility is a positive aspect that helps performing their activities, while 40.5% consider the number of families that each team has to follow to be a difficulty. Regarding work conditions, 93.2% reported the presence of professionals with a public health profile and 86.6% reported there is a lack of equipment and instruments. Of professionals who work exclusively with the FHS, 74% are community health agents. The commitment and responsibility to replace the traditional care practices should concern everyone, and there is a need for an interaction between historical, political, social, economic, and cultural factors.